2016
DOI: 10.1186/s12917-016-0895-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic features of adrenal gland lesions in dogs can aid in diagnosis

Abstract: BackgroundUltrasonography to visualize adrenal gland lesions and evaluate incidentally discovered adrenal masses in dogs has become more reliable with advances in imaging techniques. However, correlations between sonographic and histopathological changes have been elusive. The goal of our study was to investigate which ultrasound features of adrenal gland abnormalities could aid in discriminating between benign and malignant lesions. To this end, we compared diagnosis based on ultrasound appearance and histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
3
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 22 publications
0
43
3
10
Order By: Relevance
“…However, FNA does not differentiate cortical adenomas from carcinomas [13]. Nevertheless, adrenal gland size, irregularity, and vascular invasion with possible metastatic spread indicated malignancy [2]. Thus, in this report, a primary bilateral adrenal gland tumour spreading to caudal vena cava, portal lymph nodes, and liver was anticipated.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, FNA does not differentiate cortical adenomas from carcinomas [13]. Nevertheless, adrenal gland size, irregularity, and vascular invasion with possible metastatic spread indicated malignancy [2]. Thus, in this report, a primary bilateral adrenal gland tumour spreading to caudal vena cava, portal lymph nodes, and liver was anticipated.…”
Section: Discussionmentioning
confidence: 67%
“…For further evaluation of the nature of the mass of the tumour, further diagnostics (fine needle aspiration [FNA] or histology) were discussed but also declined. Yet, imaging studies had revealed several criteria indicating malignancy [2] and thus made malignant neoplasia the most likely diagnosis. However, differentials to neoplasia such as fungal disease or granuloma could not be excluded.…”
Section: Diagnosis Treatment and Further Coursementioning
confidence: 99%
“…Cães e gatos com tumor em adrenal podem ter sintomatologia mais branda ou apresentar sinais clínicos severos, portanto esses achados devem ser classificados quanto ao comportamento biológico e funcionalidade [6,13]. Em estudo recente se observou prevalência maior em cães idosos e de raça definida [17]. A ausência de sinais clínicos, alterações bioquímicas séricas e eletrolíticas compatíveis, sugerem afuncionalidade da neoplasia.…”
Section: Discussionunclassified
“…Nos exames de imagem, a aparência e tamanho da massa são os principais fatores preditores da malignidade [19]. Outros achados ultrassonográficos descritos na literatura incluem aumento irregular e lesões em adrenais direita a neoplasias malignas, bem como 82,3% de carcinomas adrenocorticais apresentaram forma nodular (único ou múltiplo) em ultrassonografia abdominal [17]. Recomenda-se ressecção cirúrgica principalmente em crescimentos acima de 6 cm, porém a decisão deve se basear também no aspecto da massa, idade do paciente e outras condições pré-existentes [10,16].…”
Section: Discussionunclassified
See 1 more Smart Citation